2022
DOI: 10.1136/lupus-2022-000738
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to FXa and thrombin in patients with SLE differentially regulate C3 and C5 cleavage

Abstract: ObjectivesThe significance of antibodies directed against activated factor X (FXa) and thrombin (Thr) in patients with SLE and/or antiphospholipid syndrome (APS) is unknown. FXa and Thr are coregulated by antithrombin (AT) and activate complement. Therefore, we studied the ability of anti activated factor X (aFXa) and/or anti-(a)Thr IgG from patients with SLE±APS to modulate complement activation.MethodsPatients with SLE±APS were selected on the basis of known aThr and/or aFXa IgG positivity, and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When the reactive center loop (RCL) of the antithrombin III anticoagulant molecule binds to the heparin-like glycosaminoglycan-rich domains of the clotting antigen, the protease cleaves the scissile P1-P1 bond of the RCL to form the P1-protease complex that results in the inactivation of the protease. Antibodies against coagulant components, on the other hand, can act as antagonists for antithrombin III binding capability to thrombin, preventing the formation of an antithrombin III-protease complex [ 35 ], inhibiting protease inactivation, and contributing to the thrombosis-inflammation interplay [ 36 ]. For instance, antibodies against FXa have been detected in patients diagnosed with SLE and APS, interfering with the antithrombin-mediated FXa inhibition and causing further thrombin generation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the reactive center loop (RCL) of the antithrombin III anticoagulant molecule binds to the heparin-like glycosaminoglycan-rich domains of the clotting antigen, the protease cleaves the scissile P1-P1 bond of the RCL to form the P1-protease complex that results in the inactivation of the protease. Antibodies against coagulant components, on the other hand, can act as antagonists for antithrombin III binding capability to thrombin, preventing the formation of an antithrombin III-protease complex [ 35 ], inhibiting protease inactivation, and contributing to the thrombosis-inflammation interplay [ 36 ]. For instance, antibodies against FXa have been detected in patients diagnosed with SLE and APS, interfering with the antithrombin-mediated FXa inhibition and causing further thrombin generation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, aThr potentiated thrombin-mediated activation of C3 and C5, whereas aFXa IgG did not increase C3 or C5 activation [49]. Having said that, the longitudinal evaluation of 58 patients with SLE ± APS did not reveal a significant association between positivity for aFXa or aThr and C3 levels or disease activity [49]; one wonders if a study of primary APS patients might show something different given the many factors that likely contribute to complement activation in SLE. A 2021 multicenter retrospective study evaluated preconception complement levels (C3 and C4) in 197 pregnant patients with APS or aPL and found that low preconception C3 and C4 were associated with a significantly higher prevalence of pregnancy losses [50 ▪ ].…”
Section: Complement Activation and Complement-mediated Injurymentioning
confidence: 99%
“…It was also shown that in patients with thrombotic APS, evidence of these circulating immune complexes was associated with thrombocytopenia, heart valve thickening/dysfunction, and lower levels of C3 and C4 [48 ▪▪ ]. A recent 2022 study evaluated the significance of antibodies directed against factor Xa and thrombin [49]. Antifactor Xa antibodies (aFXa) and antithrombin antibodies (aThr) were affinity purified from patients with SLE ± APS [49].…”
Section: Complement Activation and Complement-mediated Injurymentioning
confidence: 99%
See 2 more Smart Citations